2021
DOI: 10.1186/s13040-021-00265-8
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning based feature selection for a non-invasive breathing change detection

Abstract: Background Chronic Obstructive Pulmonary Disease (COPD) is one of the top 10 causes of death worldwide, representing a major public health problem. Researchers have been looking for new technologies and methods for patient monitoring with the intention of an early identification of acute exacerbation events. Many of these works have been focusing in breathing rate variation, while achieving unsatisfactory sensitivity and/or specificity. This study aims to identify breathing features that better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…There were no significant differences in gender, lesion location, shape, air bronchus sign, pleural traction sign, and tumor-lung interface ( P > 0.05). Studies have shown that the lobulation sign and the spicule sign are more frequently present in invasive lesions, and our findings are consistent with those reported in the literature [ 21 ]. Lobulation and spicules are the edge features of nodular lesions.…”
Section: Experiments and Analysissupporting
confidence: 93%
“…There were no significant differences in gender, lesion location, shape, air bronchus sign, pleural traction sign, and tumor-lung interface ( P > 0.05). Studies have shown that the lobulation sign and the spicule sign are more frequently present in invasive lesions, and our findings are consistent with those reported in the literature [ 21 ]. Lobulation and spicules are the edge features of nodular lesions.…”
Section: Experiments and Analysissupporting
confidence: 93%
“…We constructed the ROC curve and the precision-recall (PR) curve by calculating the TPR, FPR, and precision. The ROC curve is a probability curve with FPR on the x-axis and TPR on the y-axis at various thresholds (Kumar and Indrayan, 2011 ; Pegoraro et al, 2021 ; Sun et al, 2022 ). The AUC is then the area under the ROC curve, which is primarily used to describe the global prediction performance, where larger values indicate better performance (Tang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%